Motivasi Organisasi Ikatan Remaja Masjid (IRMAS) Ash Shohibiy Dalam Pembentukan Karakter Generasi Muda Islami Di Perumnas Mandala Kota Medan - Raudatus Sakina; Mesran Mesran; Irwansyah Irwansyah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to explore and analyze the organizational motivation of the Ash Shohibiy Mosque Youth Association (IRMAS) in shaping the Islamic character of young generations in Perumnas Mandala, Medan City, as well as to identify the supporting and inhibiting factors that influence such motivation. The background of this research stems from the importance of mosque-based youth organizations as platforms for religious, social, and leadership development rooted in Islamic values, particularly in fostering responsible, disciplined, and morally upright youth. This research employed a descriptive qualitative approach with data collection techniques including observation, in-depth interviews, and documentation. Interviews were conducted with the board of the Ash Shohibiy Mosque and the core IRMAS committee on May 16–17, 2025. Data analysis involved data reduction, data display, and conclusion drawing. The results of the study reveal that the motivation of IRMAS Ash Shohibiy members is driven by spiritual awareness, a sense of togetherness, and an internal desire to contribute to mosque activities. The character of youth involved in IRMAS shows positive development in aspects of discipline, leadership, responsibility, politeness, and social concern. Supporting factors include the support of the mosque board (BKM), a conducive religious environment, and active peer participation. Meanwhile, inhibiting factors involve limited facilities, members' busy schedules, and a lack of leadership training. This study concludes that IRMAS plays a significant role in shaping Islamic character among youth through habituation, exemplary leadership, and experiential learning in religious and social activities.